Regulation of the NF-κB-Mediated Transcription of Inflammatory Genes - Bhatt, Dev; Ghosh, Sankar (Frontiers in Immunology, 2014)
The NF-κB family of transcription factors play a central role in the inducible expression of inflammatory genes during the immune response, and the proper regulation of these genes is a critical factor in the maintenance of immune homeostasis. The chromatin environment at stimulus-responsive NF-κB sites is a major determinant in transcription factor binding, and dynamic alteration of the chromatin state to facilitate transcription factor binding is a key regulatory mechanism. NF-κB is in turn able to influence the chromatin state through a variety of mechanisms, including the recruitment of chromatin modifying co-activator complexes such as p300, the competitive eviction of negative chromatin modifications, and the recruitment of components of the general transcriptional machinery. Frequently, the selective interaction with these co-activators is dependent on specific post-translational modification of NF-κB subunits. Finally, the mechanisms of inducible NF-κB activity in different immune cell types seem to be largely conserved. The diversity of cell-specific NF-κB mediated transcriptional programs are established at the chromatin level during cell differentiation by lineage defining transcription factors. These factors generate and maintain a cell-specific chromatin landscape that is accessible to NF-κB, thus restricting the inducible transcriptional response to a cell-appropriate output.